'Cultural Persistence' of Health Capital: Evidence from European Migrants - Joan Costa-i-Font; Azusa Sato (Center for Economic Studies and ifo Institute (CESifo), 2016)
Culture is an under-studied determinant of health production and seldom measured. This paper empirically examines the persistence and association of health capital assessments of first and second-generation migrants with that of their ancestral countries. We draw on European data from 30 countries, including over 90 countries of birth and control for timing of migration, selective migration and other controls including citizenship and cultural proxies. Our results show robust evidence of cultural persistence of health assessments. Culture persists, rather than fades, and further, appears to strengthen over generations. We estimate a one standard deviation increase in ancestral health assessment increases first generation migrant's health assessments by an average of 16%, and that of second generation migrants between 11% and 25%. Estimates are heterogeneous by gender (larger for males) and lineage (larger for paternal lineage).
Keywords: I18; H23; Z13; 330; assimilation; health; health assessments; cultural persistence; first generation migrant; second generation migrant